Trained Immunity in Perivascular Adipose Tissue of Abdominal Aortic Aneurysm—A Novel Concept for a Still Elusive Disease - Piacentini, Luca; Vavassori, Chiara; Colombo, Gualtiero I. (Frontiers in Cell and Developmental Biology, 2022)
Abdominal aortic aneurysm (AAA) is a chronic, life-threatening vascular disease whose only therapeutic option is a surgical repair to prevent vessel rupture. The lack of medical therapy results from an inadequate understanding of the etiopathogenesis of AAA. Many studies in animal and human models indicate a 'short-circuiting' of the regulation of the inflammatory-immune response as a major player in the AAA chronic process. In this regard, perivascular adipose tissue (PVAT) has received increasing interest because its dysfunction affects large arteries primarily through immune cell infiltration. Consistently, we have recently produced evidence that innate and adaptive immune cells present in the PVAT of AAAs contribute to sustaining a damaging inflammatory loop. However, it is still unclear how the complex crosstalk between adaptive and innate immunity can be self-sustaining. From our perspective, trained immunity may play a role in this crosstalk. Trained immunity is defined as a form of innate immune memory resulting in enhanced responsiveness to repeated triggers. Specific innate stimuli and epigenetic and metabolic reprogramming events induce and shape trained immunity in myeloid progenitor cells improving host defense, but also contributing to the progression of immune-mediated and chronic inflammatory diseases. Here we present this hypothesis with data from the literature and our observations to support it.